Catalogue of Psychodidae (Diptera) in the Medical Importance Arthropod Collection (CAIM), InDRE, Secretaria de Salud, Mexico. - godínez-Álvarez, Adriana; Ibáñez-Bernal, Sergio (Instituto de Ecología, A.C., 2010)
A catalogue of specimens belonging to the family Psychodidae (Diptera) deposited in the Medical Importance Arthropod Collection (CAIM) of the Instituto de Diagnóstico y Referencia Epidemiológicos (InDRE), Mexico is presented. In this collection the psychodids are represented by 2459 specimens of three subfamilies, six genera and 55 species. A total of 28 species are from 20 states of Mexico (Chiapas, Coahuila, Colima, Distrito Federal, Estado de Mexico, Guerrero, Jalisco, Michoacan, Morelos, Nayarit, Nuevo Leon, Oaxaca, Puebla, Quintana Roo, San Luis Potosi, Sonora, Tabasco, Tamaulipas, Veracruz, and Yucatan), and 27 species (172 specimens) proceed from other American countries like Argentina, Brazil, Costa Rica, United States of America, French Guiana, Honduras, Virgin Islands, Panama, Peru, Puerto Rico, Trinidad, and Venezuela.